Nigrostriatal Dopaminergic Dysfunction and Altered Functional Connectivity in REM Sleep Behavior Disorder With Mild Motor Impairment - Yamada, Gohei; Ueki, Yoshino; Oishi, Naoya; Oguri, Takuya; Fukui, Ayako; Nakayama, Meiho; Sano, Yuko; Kandori, Akihiko; Kan, Hirohito; Arai, Nobuyuki; Sakurai, Keita; Wada, Ikuo; et al. (Frontiers in Neurology, 2019)
Rapid eye movement sleep behavior disorder is a parasomnia characterized by symptoms of dream enactment and loss of muscle atonia during rapid eye movement sleep. Mild motor impairment is present in some patients with rapid eye movement sleep behavior disorder and it is presumed to be a risk factor for conversion to synucleinopathies. The purpose of this study was to identify patients with mild motor impairment by evaluating finger tapping and to investigate its pathophysiology. Twenty-three patients with rapid eye movement sleep behavior disorder and 20 healthy control subjects were recruited in this study. We accurately evaluated finger tapping including amplitude and peak open and close speeds with a magnetic sensing device and identified patients with mild motor impairment. Moreover, we performed 123I-2β-carbomethoxy-3β-(4-iodophenyl) nortropane single-photon emission computed tomography and resting-state functional magnetic resonance imaging. 123I-2β-carbomethoxy-3β-(4-iodophenyl) nortropane uptake for the bilateral caudate, anterior putamen, and posterior putamen was calculated, and the resting-state functional connectivity of the sensorimotor network was analyzed. Using finger tapping parameters, we identified eight patients with mild motor impairment. In patients with mild motor impairment, all finger tapping parameters were significantly impaired compared to those in patients with normal motor function, while there were no significant differences in the Unified Parkinson's Disease Rating Scale part III score. 123I-2β-carbomethoxy-3β-(4-iodophenyl) nortropane uptake in the right posterior putamen, bilateral anterior putamen, and caudate was significantly lower than that in healthy controls or patients with rapid eye movement sleep behavior disorder with normal motor function. The patients with mild motor impairment also exhibited decreased cortico-striatal and increased cortico-cerebellar functional connectivity compared to healthy controls or patients with normal motor function. Our results showed that mild motor impairment in rapid eye movement sleep behavior disorder evaluated by the finger tapping task was associated with mild nigrostriatal dopaminergic dysfunction as well as alterations in the resting-state sensorimotor network. Although longitudinal follow up is necessary, such patients may be at higher risk of short-term conversion to synucleinopathies.